Respiratory supercomplexes act as a platform for complex III‐mediated maturation of human mitochondrial complexes I and IV. (8th January 2020) - Protasoni, Margherita; Pérez‐Pérez, Rafael; Lobo‐Jarne, Teresa; Harbour, Michael E; Ding, Shujing; Peñas, Ana; Diaz, Francisca; Moraes, Carlos T; Fearnley, Ian M; Zeviani, Massimo; Ugalde, Cristina; Fernández‐Vizarra, Erika
Abstract: Mitochondrial respiratory chain (MRC) enzymes associate in supercomplexes (SCs) that are structurally interdependent. This may explain why defects in a single component often produce combined enzyme deficiencies in patients. A case in point is the alleged destabilization of complex I in the absence of complex III. To clarify the structural and functional relationships between complexes, we have used comprehensive proteomic, functional, and biogenetical approaches to analyze a MT‐CYB‐deficient human cell line. We show that the absence of complex III blocks complex I biogenesis by preventing the incorporation of the NADH module rather than decreasing its stability. In addition, complex IV subunits appeared sequestered within complex III subassemblies, leading to defective complex IV assembly as well. Therefore, we propose that complex III is central for MRC maturation and SC formation. Our results challenge the notion that SC biogenesis requires the pre‐formation of fully assembled individual complexes. In contrast, they support a cooperative‐assembly model in which the main role of complex III in SCs is to provide a structural and functional platform for the completion of overall MRC biogenesis. Synopsis: The mitochondrial respiratory chain (MRC), necessary for aerobic cellular energy transduction in eukaryotic cells, consists of five large enzyme complexes that can assemble into larger supramolecular structures called supercomplexes (SCs). Biogenesis of the human MRC requires the cooperative and interdependent action of respiratory SCs. Complex III is a master regulator of MRC maturation and SC formation. Lack of respiratory complex III halts the assembly of complex I by preventing the incorporation of the NADH‐module, but it does not induce the degradation of fully assembled complex I. Coenzyme Q and oxidoreductase activity of complex III are required for the maturation of complex I. Mis‐assembly of complex III affects the biogenesis of complex IV as it causes the sequestration of unassembled complex IV subunits into complex III preassemblies. Complex I, III and IV assemble in a cooperative way, interacting with each other prior to the formation of the individual complexes. Abstract : Biogenesis of the human mitochondrial respiratory chain requires the cooperative and interdependent action of respiratory supercomplexes.